Regulation of immune response with signaling lymphocyte activation molecule related receptors: Review - Demir, Nesrin; Ilhan, Fulya (Ortadogu Ad Pres & Publ Co, 2007)
The (SLAM)-related receptors (SRR) group includes CD150 (SLAM), CD244 (2134), CD84, CD299 (Ly-9), NTB-A (Ly-108), and CD319 (CRACC: CD2-like receptor-activating cytotoxic cells). Several adaptive proteins including SLAM associated protein (SAP) have a major role in the signal transduction of the SRR group. These receptors are expressed on many immune system cells. SAP deletion causes many defects in the cellular signaling. X-linked lymphoproliferative syndrome (XLP), which is a severe immune disorder, is the result of SAP deficiency. SRR receptors also may play a significant role in autoimmune diseases such as systemic lupus erythematosis (SLE), rheumatoid arthritis (RA) and in tuberculosis. Here, we review the current understanding of SRR function in different immune cells.
Sinyal olu§turan lenfosit aktivasyon molekül i?lişkili reseptörler aracili?i ile immün cevabin düzenlenmesi
Keywords: lymphoproliferative disorders; SH2D1A protein; human; signal transduction